2021
DOI: 10.1161/hypertensionaha.121.17323
|View full text |Cite
|
Sign up to set email alerts
|

Albuminuria Testing in Hypertension and Diabetes: An Individual-Participant Data Meta-Analysis in a Global Consortium

Abstract: Albuminuria is an under-recognized component of chronic kidney disease definition, staging, and prognosis. Guidelines, particularly for hypertension, conflict on recommendations for urine albumin-to-creatinine ratio (ACR) measurement. Separately among 1 344 594 adults with diabetes and 2 334 461 nondiabetic adults with hypertension from the chronic kidney disease Prognosis Consortium, we assessed ACR testing, estimated the prevalence and incidence of ACR ≥30 mg/g and developed risk models for ACR ≥30 mg/g. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 31 publications
(42 reference statements)
2
60
0
2
Order By: Relevance
“…MHS insures and provides care to 26% of the Israeli population, but its representativeness among the Jewish population who is obliged for military service is ≈40%. The MHS chronic disease registry, part of the chronic kidney disease prognosis consortium, 14 was established in 2001 and collects data from electronic medical records, laboratory results, pharmacy prescriptions, and purchase logs. Laboratory data are analyzed in a central laboratory.…”
Section: The Chronic Kidney Disease Registry Of Maccabi Health Servicesmentioning
confidence: 99%
“…MHS insures and provides care to 26% of the Israeli population, but its representativeness among the Jewish population who is obliged for military service is ≈40%. The MHS chronic disease registry, part of the chronic kidney disease prognosis consortium, 14 was established in 2001 and collects data from electronic medical records, laboratory results, pharmacy prescriptions, and purchase logs. Laboratory data are analyzed in a central laboratory.…”
Section: The Chronic Kidney Disease Registry Of Maccabi Health Servicesmentioning
confidence: 99%
“…These data are important to inform on the need of measuring albuminuria in high-risk populations and to better interpret results of ACR monitoring at the bedside. Still, low rates of albuminuria monitoring and detection are features of all health systems globally [22].…”
Section: Prevalence and Recognition Of Ckdmentioning
confidence: 99%
“…Although various risk factors could affect the development of albuminuria, abundant studies have confirmed that raised blood pressure and dysglycaemia are two critical risk factors for albuminuria ( 8 11 ). Cumulative evidence emphasizes that control of glycated hemoglobin (HbA1c) and systolic blood pressure (SBP) are significant in decreased ACR for both T2DM and Diabetic kidney disease (DKD) patients ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the studies on the risk relationship between SBP and ACR have also been extensively reported. A meta-analysis included 31 cohorts in the world and demonstrated that each 20 mmHg increase in SBP was associated with a 1.5-fold higher prevalence of albuminuria (ACR ≥ 30 mg/g) in diabetes ( 11 ). It was also reported that only SBP ≤ 120 mmHg was associated with the lowest risk of new-onset microalbuminuria ( 16 ).…”
Section: Introductionmentioning
confidence: 99%